If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=25P-(10P+250))
We move all terms to the left:
-(25P-(10P+250)))=0
We calculate terms in parentheses: -(25P-(10P+250))), so:P=0/-15
25P-(10P+250))
We get rid of parentheses
25P-10P-250)
We add all the numbers together, and all the variables
15P
Back to the equation:
-(15P)
P=0
| 7x+3+4x+24=180 | | 12c-16=16 | | 9y+-23=40 | | 1/298n+6)=4n+3 | | 11k-10k=17 | | 4.2+z=11.2/6.7.8 | | 14(v+4)-2v=4(3v+3)-20 | | 5p-5p+4p=4 | | 5h-2(3/2h+4=10) | | 6t+4t+t-9t-t=18 | | 1/3(z+4)-6=2/3(5-z)= | | 2(6-2x)+6=-9x-6+5x | | 2x+4-3x=-1 | | 15r+r-13+r=20 | | 8r-7=7 | | Nx3=-4 | | (-4+5b)=16 | | 3x+(2-4x)=0 | | d+58=180 | | 12*y=72 | | 3-2g=- | | 2x+5+7x-14=180 | | -1.3+y/7=18.8 | | 20x2-6x=-8 | | 6w+5=17 | | g÷2=4 | | 3.4x-19.1=9.1 | | -8x-63=0.25-3 | | a+58=180 | | 243=3^x+3 | | 2,3d=6 | | 3t^2+14t+16=0 |